Iskolák a Tanácsköztársaság idején és a baranyai felekezeti tanítók felelősségre vonása - Niklai, Patrícia Dominika (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2020)
The Hungarian Soviet Republic reorganized schools fundamentally. Efforts were made to reduce the influence of the churches by seeking to achieve religious neutrality on an ideological basis. To do so, schools - not only the institutions maintained by the denominations, but also by the municipality, associations and private persons - were socialized, with the state playing the primary role in education. The Revolutionary Governing Council (government of the Hungarian Soviet Republic) and the Commissariat for Public Education - which replaced the Ministry of Religion and Public Education - took measures to take over schools by the State and displace religion. They strove to re-educate teachers in a communist spirit; priests, nuns, and monks were continued to be employed as teachers only, if they declared themselves secular. In addition to nationalization, they wanted to solve the problems of the education immediately with radical solutions. In several cases, this may have gained the support of teachers, whose vast majority – as presented in various forums – were basically dissatisfied with their previous (financial and social) situation. After the fall of the system, there was a sharp political shift with an even more intense emphasis on religious education. Because of that, the investigation of teachers who supported, or at least served the measures of the Hungarian Soviet Republic proved to be essential. One of the conclusions based on the documents revealed by the disciplinary proceedings is that the denominational teachers, whose task was the religious and moral education of the children, tended to give a firm voice to their political orientation aside from this. However, as several cases show, these prosecutions may have served as a means of personal revenge when most teachers were investigated and, in many cases, false or unfounded charges were reported.